Psychological Disorders among Iranian Infertile Couples Undergoing Assisted Reproductive Technology (ART) - Mansoureh KARIMZADEH; Nasser SALSABILI; Firouzeh AKBARI ASBAGH; Robab TEYMOURI; Golamreza POURMAND; Tahereh SOLEIMANIEH NAEINI (Tehran University of Medical Sciences, 2017)
Background: Worldwide, infertility affects 10%-15% of couples and most of them seek medical help including Assisted Reproductive Technology (ART) treatments. Undergoing ART treatments create many physical and emotional burdens. This study examined the psychological consequences of infertility in Iranian infertile males and females as well as their spouses, unlike previous studies that examined mainly females with infertility. Methods: Subjects in this descriptive analytical design were recruited from the IVF Department of Mirza Koochak Khan Hospital and the Rouyesh Infertility Treatment Center of Tehran, Iran between Aug 2014 and Sep 2015. Overall, 256 couples (64% response rate), consisting of 78 infertile male and their spouses and 50 infertile female and their spouses, were included in this research. The psychological disorders were measured by the Persian version of Symptoms Checklist-90-Revised and Cattle Inventory. Results: Psychological disorders of infertile couples are significantly associated with increasing age, higher education, longer duration of infertility and unemployment (P<0.05). Prevalence of anxiety, depression, hypochondriasis and paranoia in infertile females and spouses of infertile males were significantly higher than husbands of infertile females (P<0.05). Obsession was more sever in infertile females was significantly greater than infertile males (P=0.01). Depression was significantly lower in infertile males than their spouses (P=0.016). Conclusion: Iranian infertile females and spouses of infertile males experienced more psychological disorders than infertile males and spouses of infertile females. These results may be due to the impact of cultural beliefs and gender roles in Iranian society. Anxiety, depression, obsession, paranoia and hypochondriasis should be addressed before any ART treatments.